2014
DOI: 10.1159/000366036
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment in Early Colorectal Cancer: Histological and Molecular Markers

Abstract: The pathological examination of early colorectal cancer specimens, in particular ‘malignant polyps', provides important prognostic information. The depth of invasion into the submucosal layer assessed according to the Haggitt (for pedunculated lesions) or Kikuchi (for nonpolypoid lesions) classification systems or by direct measurement has been associated with the risk of lymph node metastasis. Angioinvasion, in particular lymphatic invasion, budding, tumor differentiation or grade, and resection margin status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Moreover, earlier studies reported that the risk of LNM is extremely low in deep invasive T1 CRC in the absence of other high-risk factors 29–32. Evolving molecular diagnostics have the potential to improve the prediction of LNM, and may expand the number of curative local minimal invasive resections 33. Furthermore, increased experience with en bloc endoscopic resection techniques such as ESD and full-thickness resection, and a better infrastructure to expert centres once cancer is suspected, might increase the number of en bloc resections with negative resection margins.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, earlier studies reported that the risk of LNM is extremely low in deep invasive T1 CRC in the absence of other high-risk factors 29–32. Evolving molecular diagnostics have the potential to improve the prediction of LNM, and may expand the number of curative local minimal invasive resections 33. Furthermore, increased experience with en bloc endoscopic resection techniques such as ESD and full-thickness resection, and a better infrastructure to expert centres once cancer is suspected, might increase the number of en bloc resections with negative resection margins.…”
Section: Discussionmentioning
confidence: 99%
“…An ideal predictive model would therefore identify those patients most likely to benefit from resection while preventing an excess of unnecessary operations. Previous studies have reported an array of ‘high-risk’ pathological features, including polyp size,20 location,21 lymphovascular invasion,12 poor differentiation,22 tumour budding,23 close or involved margins,12 23 sessile morphology24 and depth of submucosal invasion. The latter, in particular, is widely regarded as an important determinant of the likelihood of lymph node metastases and can be assessed in a number of different ways.…”
Section: Discussionmentioning
confidence: 99%
“…The depth of infiltration by budding cells is currently shown to influence the frequency of lymph node metastases. Submucosal invasion <1000 μm (1 mm) is related with a low risk for nodal metastases [ 35 , 40 - 42 ], irrespective of the budding grade. However, the risk of nodal involvement in tumors invading beyond 1000 μm into submucosa (≥sm2), is related to the grade of TB, being exceptionally high in high-grade budding [ 44 ].…”
Section: Tbmentioning
confidence: 99%